Family Relations, Alexithymia, and Eating Attitudes in Pakistani University Student - Bibi, Anam; Wasim, Hamza; Saleem, Abdul Raffay (Journal of Applied Research and Multidisciplinary Studies, 2025)
This study was done to examine the relationship between family relations, alexithymia, and eating attitudes in university students. It was hypothesized that a relationship is likely to be there between family relations, alexithymia, and eating attitudes in university students. Further, family relations, and alexithymia are likely to predict eating attitudes in university students. It was also hypothesized that there would be gender differences across family relations, alexithymia, and eating attitudes in university students. This was a correlation study with cross-sectional research design. Non-probability convenient sampling strategy was used to recruit N=230 university students. Assessment measures were self-constructed demographic information sheet, Index of Family Relations (Hudson, 1993), Toronto Alexithymia Scale (Bagby et al., 1986), Eating Attitudes Test (Garner & Garfinkel, 1979). Results reveal that family relations were positively correlated with alexithymia and eating attitudes and alexithymia was also positively correlated with eating attitudes in university students. There were no gender differences in family relations, alexithymia, and eating attitudes in university students. This study has implications for family, therapists, university counselors, and policy makers.